On Current Developments in Partial Differential Equations (Communications in Mathematical Research, 2020)
The first part of this article is an overview on some recent major developments in the field of analysis and partial different equations. It is a brief presentation given by the author at a round table discussion. The second part is a supplement of various details provided by several outstanding researchers on subjects.
Keywords: Partial differential equations; harmonic analysis; geometric measure theory.